Engineering Efficient Retinal Pigment Epithelium Differentiation From Human Pluripotent Stem Cells. (1st October 2014) - Lane, Amelia; Philip, Lissa Rachel; Ruban, Ludmila; Fynes, Kate; Smart, Matthew; Carr, Amanda; Mason, Chris; Coffey, Pete
Abstract : Human embryonic stem cell lines produce a number of clusters of pigmented retinal pigment epithelium (RPE) cells when allowed to spontaneously differentiate, but the timing and efficiency of differentiation is highly variable. Neural induction using dorsomorphin significantly enhanced the RPE yield in one cell line but significantly reduced it in another, underlining the necessity of tailoring differentiation protocols to suit the innate properties of different cell lines. Abstract: Human embryonic stem cells (hESCs) are a promising source of retinal pigment epithelium (RPE) cells: cells that can be used for the treatment of common and incurable forms of blindness, such as age-related macular degeneration. Although most hESC lines will produce a number of clusters of pigmented RPE cells within 30–50 days when allowed to spontaneously differentiate, the timing and efficiency of differentiation is highly variable. This could prove problematic in the design of robust processes for the large scale production of RPE cells for cell therapy. In this study we sought to identify, quantify, and reduce the sources of variability in hESC-RPE differentiation. By monitoring the emergence of pigmented cells over time, we show how the cell line, passaging method, passage number, and seeding density have a significant and reproducible effect on the RPE yield. To counter this variability, we describe the production of RPE cells from two cell lines in feeder-free, density controlled conditions using single cell dissociation and seeding that is more amenable to scaled up production. The efficacy of small molecules in directing differentiation toward the RPE lineage was tested in two hESC lines with divergent RPE differentiation capacities. Neural induction by treatment with a bone morphogenetic protein inhibitor, dorsomorphin, significantly enhanced the RPE yield in one cell line but significantly reduce it in another, generating instead a Chx10 positive neural progenitor phenotype. This result underlines the necessity to tailor differentiation protocols to suit the innate properties of different cell lines.